Neuroprotective properties of Nigella sativa (L.) seeds and Murraya koenigii (L.) spreng leaves extracts in experimental animal models - Babar, Zahir Uddin Mohammed (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2016)
The anti-oxidant properties of both M. koenigii leaves and N. sativa seeds extracts have been associated with many of their pharmacological activities including neuroprotective potentials in experimental animal models. The purpose of the current study was to analyze the anti-oxidant properties and assess neuroprotective effects of the extracts in zebrafish and rat models. The solubility and thin layer chromatographic (TLC) techniques have been used as classical methods for physicochemical characterization. Experimental neuro-excitotoxicity was induced by AlCl3 (20 μg/mL) and MSG (475 μg/mL) in zebrafish embryos and larvae models through immersion technique while neuroinflammation by two-vessel occlusion (2VO) in healthy male Sprague Dawley rats. It was confirmed that N. sativa oil (NSO) and water soluble extract (WSE) of N. sativa seeds have different physicochemical properties while WSE has exhibited similar Rf value of 0.95 to that of both Tualang and Kelulut honeys. The presence of thymoquinone (TQ) in NSO was confirmed at (Rf = 0.86) compared to the standard TQ. M. koenigii leaves extract (MKLE) has showed the most potent anti-oxidant property with (IC50=7.63 μg/mL) followed by WSE (IC50= 33.32 μg/mL), NSO alone (IC50= 73.67 μg/mL) and NSO + WSE (IC50= 78.22 μg/mL) respectively against 1, 1-diphenyl-2-hydrazyl (DPPH). Both NSO (0.125 μg/mL) and WSE (80 μg/μmL) have shown to protect the deformities of neurotoxicity significantly (P < 0.05) in AlCl3-induced neurotoxic zebrafish embryo model only after 48 hours of post-induction (hpi). In addition, WSE has also exhibited to protect the deformities of excitotoxicity in both of MSG-induced embryos (50 µg/mL) and larvae (80 µg/mL) models significantly (P < 0.05) compared to that of MSG (475 µg/mL) after 48 hpi. 24 healthy adult male Sprague Dawley rats were randomly divided into four groups (n=6); Healthy Control (HC); 2VO-untreated (2VO); 2VO+NSO treated (NSO) and 2VO+MKLE treated (MKLE). The NSO (100%, 1 mL/kg of b.w) and MKLE (50 mg/kg/day orally) groups were pre-treated for 10 days prior to 2VO surgery and continued until all animals were sacrificed at the end of 10th postoperative week. Total RNA was extracted, purified and relatively quantified as per relative normalized gene expression (∆∆Cq) of two-step RT-qPCR assay with pre-designed QuantiTect® primers. There were significant (P<0.01) folds of difference in GFAP mRNA expression of NSO and HC groups as compared to that of untreated 2VO while there was no significant (P > 0.05) of GFAP mRNA expressions for NSO vs. HC and MKLE vs. 2VO. Conversely, GFAP mRNA expression for MKLE was significantly (P < 0.05) different from NSO group. There was a significantly (P < 0.05) down-regulated MAP2 mRNA expression in both 2VO and NSO groups as compared to that of HC. Yet, the MAP2 mRNA expressions in both NSO and MKLE treated groups were not significantly different (P > 0.05) to that of 2VO untreated. The overall findings suggest that MKLE could have mild neuroprotective potential via glutamate receptors only while N.sativa seeds extract could have superior neuroprotective activity via both of glutamate and MI muscarinic acetylcholine receptors. It is proposed that zebrafish embryo model of 24 hpf developed in this study could be used as a reliable tool to investigate neuroprotective potentials of any other crude extract or leading anti-AD drug in neurobehavioral sciences.